2017
DOI: 10.1371/journal.pone.0173262
|View full text |Cite
|
Sign up to set email alerts
|

The effect of paclitaxel-eluting covered metal stents versus covered metal stents in a rabbit esophageal squamous carcinoma model

Abstract: BackgroundThe use of self-expanding metallic stents (SEMSs) is the current treatment of choice for malignant gastrointestinal obstructions. However, these stents can promote only drainage and have no antitumor effect. Some studies have reported that drug-eluting SEMSs may have tumor inhibition potential. The aim of this study was to evaluate the efficiency and safety of paclitaxel-eluting SEMSs (PEMSs) in rabbit esophageal cancer models.Materials and methodsA PEMS was covered with a paclitaxel-incorporated mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
(31 reference statements)
0
17
0
1
Order By: Relevance
“…For those patients with inoperable esophageal malignancies, using a SEMS to mechanically open the blocked esophagus for drinking and feeding has become the primary palliative therapy of dysphagia [6]. Recently, drug-eluting self-expanding metallic stents (DE-SEMS) have been attempted with some efficacy for the management of occlusion of the esophagus beyond just palliative procedure [7, 8]. DE-SEMS, a drug-loaded polymer membrane coated SEMS, provides both the mechanical support to expand the blocked esophagus, and the released anticancer drug to inhibit tumor growth, which has been proven to prolong patient life-span[11].…”
Section: Self-expandable Stentsmentioning
confidence: 99%
See 2 more Smart Citations
“…For those patients with inoperable esophageal malignancies, using a SEMS to mechanically open the blocked esophagus for drinking and feeding has become the primary palliative therapy of dysphagia [6]. Recently, drug-eluting self-expanding metallic stents (DE-SEMS) have been attempted with some efficacy for the management of occlusion of the esophagus beyond just palliative procedure [7, 8]. DE-SEMS, a drug-loaded polymer membrane coated SEMS, provides both the mechanical support to expand the blocked esophagus, and the released anticancer drug to inhibit tumor growth, which has been proven to prolong patient life-span[11].…”
Section: Self-expandable Stentsmentioning
confidence: 99%
“…A local, more targeted release of an anticancer drug from a bilayered or multilayered drug-releasing films demonstrated enhanced efficacy of anticancer drugs, prevented or reduced the side effects associated with systemic administration of an anticancer drug, such as paclitaxel, 5-fluorouracil, and gemcitabine [7, 11, 6062]. Therefore, this type of drug-eluting stent has potential for improving inhibition of esophageal tumor growth.…”
Section: Self-expandable Stentsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Zhang et al reported the effects of paclitaxel-eluting metallic stent (PEMS) in normal esophagus and in a rabbit esophageal squamous carcinoma model in their serial studies. 55,56 Their results showed that PEMS slowed tumor growth and thereby can serve as an alternative tool for esophageal cancer. However, the molecular mechanism of the antitumor effect was not clear in their study.…”
Section: Drug-eluting Stentsmentioning
confidence: 99%
“…Разработана двуслойная полимерная пленка из биосовместимого полиуретана с включением доцетаксела, которая может стать покрытием для СМС [46]. Исследования стентов с полимерным покрытием, содержащим паклитаксел, на кроликах продемонстрировали впечатляющее уменьшение размеров и объема опухоли [47,48]. В другом исследовании на свиной модели были протестированы стенты с покрытием, содержащим 5-фторурацил или паклитаксел, причем удалось достичь высокой концентрации действующего вещества в опухоли без повреждения слизистой пищевода [49].…”
unclassified